Analysing the heterogeneity of traveller mode choice preference using a random parameter logit model from the perspective of principal-agent theory. Issue 4 (1st January 2014) - Mehbub Anwar, A.H.M.; Tieu, Kiet; Gibson, Peter; Win, Khin Than; Berryman, Matthew J.
When travellers entrust their desire for a transport mode that is customer-focused (i.e., reliable) to the Transport for NSW (TfNSW), this creates a metaphorical contract between travellers and the TfNSW, known as an agency contract . This contract is often characterised by agency uncertainty because both are most likely to act in their own self-interest. It can be assumed that where there is a high use of public transport, the TfNSW is performing the entrusted tasks as per travellers' demand, which indicates an improvement in agency uncertainty. On the other hand, where there is a high use of private transport, it is likely that the TfNSW is acting largely in its own self-interest, and the agency problem remains unresolved. From the results, it is shown that the probability of car use is significantly higher than public transport, which indicates that an agency problem exists in the traveller-TfNSW relationship. It is recommended that integrating traveller preferences in transport projects would help to resolve this problem.